Religion and Theatrical Drama - Bouchard, Larry D.; Gillespie, Charles A. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
With an introduction on how to redefine our thinking about religion and theatrical drama, these nine essays on contemporary and classic plays rehabilitate the link between theatrical performance and dramatic stories for the study of religion. These new and distinctively interdisciplinary perspectives will be of interest to scholars working in the fields of religion, theology, theatre and performance studies, literary studies, and philosophy.